Mechanical Properties of Nb-Ti-Ni Alloy Membranes for Hydrogen Permeation. Issue 6 (June 2016) - Huaigang, Zhang; Zhongmin, Wang; Fei, Liu; Jianqiu, Deng; Huaiying, Zhou
Abstract: The microstructure and the mechanical property of Nb-Ti-Ni alloy membranes for hydrogen permeation were investigated. XRD and SEM were employed to characterize the structures of Nb-Ti-Ni alloys, and the bending property of the alloy membranes was measured by three-point bending tests. The results indicate that the as-prepared alloy is mainly composed of two phases, i.e. the primary bcc-Nb(Ni, Ti) solid solution phase, and [bcc-Nb(Ni, Ti)+ β 2-NiTi] eutectic phase. The former acts as functional cell for hydrogen permeation and the later is structural cell to keep the stability of alloy membrane. Mechanical properties of Nb-Ti-Ni alloy membranes have been improved to a certain degree by magnetic heat-treatment (MHT) along the three directions (0°, 45° and 90°). An obvious improvement has been made in the case of N7 sample by MHT at both of 0° and 45°, and in the case of N5 sample by MHT at 90° angle. MHT can lead to the change of grain sizes and grain orientations. In the case of MHT at 0° angle, a tiny bar-like region (consisting of eutectic phase) is formed and spreads along the direction of membrane surface, while some oral-like (or spot-like) region is regularly arranged on the surface, and the region extends vertically to the surface in the case of MHT at 90° angle. It is suggested that suitable MHT is beneficial to the improvement of the bending property of Nb-Ti-Ni alloy membranes.